A jump in the atrioventricular conduction curve is not caused by a switch from fast pathway to slow pathway conduction - Zhang, Youhua (Frontiers in Physiology, 2024)
Background: A jump in the atrioventricular (AV) conduction curve is the current clinical criterion of dual pathway electrophysiology. However, the assumption that a jump indicates a switch from fast pathway (FP) to slow pathway (SP) conduction remains unconfirmed. This study was to investigate whether a jump indeed indicates a transition from FP to SP conduction and if not, what is the potential cause.Methods: Eighty-one experimental records from rabbit AV nodal preparations containing the following data were analyzed. 1. had at least one AV conduction curve, and 2. had recording of His electrogram alternans (a validated new index of dual pathway conduction). Most cases also had intracellular action potential recordings from the AV nodal fibers.Results: There were 11 (13%) of 81 preparations showing a jump in the AV conduction curve.The jumps always occurred after the FP to SP transition. The FP-SP transition occurred at prematurity of 196±39ms versus the jump at 114±13ms (P<0.001). The beat with a jump showed a SP-FP-pattern in 7 and a SP-SP-pattern in 4 preparations. The jumps were always associated with and most likely caused by the formation of intranodal/nodal-atrial reentry and its subsequent conduction, rather than a switch from FP to SP conduction.In contrast to what it has been assumed, a transition from FP to SP conduction does not produce a jump in the AV conduction curve. A jump in the AV conduction curve is most likely caused by the formation of intranodal/nodal-atrial reentry and its subsequent conduction.